При = -1, 5.
(x+6)×(x-6) - (x + 11)^2​

svitlanatopp08vqs svitlanatopp08vqs    1   13.03.2021 16:46    0

Ответы
karinayatskevioz1zkj karinayatskevioz1zkj  13.03.2021 16:50

вроде правильно , если правильно сделай ответ лучшим


При = -1, 5.(x+6)×(x-6) - (x + 11)^2​
ПОКАЗАТЬ ОТВЕТЫ
dudulya1 dudulya1  13.03.2021 16:50

Объяснение:

(х+6)(х-6)-(х+11)^2=

=х^2-36-(х^2+22х+121)=

=х^2-36-х^2-22х-121=

= - 22х-157

При х= - 1,5

-22×(-1,5)-157=33-157= - 124

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра